2007
DOI: 10.1093/molbev/msm182
|View full text |Cite
|
Sign up to set email alerts
|

WOX Gene Phylogeny in Poaceae: A Comparative Approach Addressing Leaf and Embryo Development

Abstract: The phylogeny based on the homeodomain (HD) amino acid sequence of the WOX (WUSCHEL-related homeobox gene family) was established in the 3 major radiations of the Poaceae family: Pooideae (Brachypodium distachyon), Bambusoideae (Oryza sativa), and Panicoideae (Zea mays). The genomes of all 3 grasses contain an ancient duplication in the WOX3 branch, and the cellular expression patterns in maize and rice indicate subfunctionalization of paralogues during leaf development, which may relate to the architecture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
109
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(122 citation statements)
references
References 32 publications
8
109
0
5
Order By: Relevance
“…Whereas WOX2 functions in the apical embryo domain, WOX5 and NUC homologs accumulate in the basal regions of developing embryos, where they eventually specify distinct root domains (Haecker et al, 2004;Levesque et al, 2006;Nardmann et al, 2007). These root-specific transcription factors were probably detected in our transition-stage samples because these microdissected domains included both the apical and basal regions of the embryo ( Figures 1N and 1T), whereas only shoot domains were isolated from later stages.…”
Section: Elaboration Of the First Three Lateral Organsmentioning
confidence: 97%
See 4 more Smart Citations
“…Whereas WOX2 functions in the apical embryo domain, WOX5 and NUC homologs accumulate in the basal regions of developing embryos, where they eventually specify distinct root domains (Haecker et al, 2004;Levesque et al, 2006;Nardmann et al, 2007). These root-specific transcription factors were probably detected in our transition-stage samples because these microdissected domains included both the apical and basal regions of the embryo ( Figures 1N and 1T), whereas only shoot domains were isolated from later stages.…”
Section: Elaboration Of the First Three Lateral Organsmentioning
confidence: 97%
“…In Arabidopsis, WOX2 and WOX9 (also known as STIMPY) are also expressed before SAM initiation and specify the apical-basal axis of the embryo (Haecker et al, 2004;Wu et al, 2007;Breuninger et al, 2008). Previous reports in maize revealed that WOX2A transcripts accumulate in the apical cap of the proembryo before localizing to the germinal face of the transition-stage embryo (Nardmann et al, 2007). The accumulation of WOX2A and WOX9B transcripts in the premeristematic maize proembryo is consistent with a conserved function of these WOX putative paralogs in establishing apicalbasal domains in the maize embryo before SAM initiation.…”
Section: Establishing a Meristemmentioning
confidence: 99%
See 3 more Smart Citations